Vida privada de um homem público na década de 1950: uma liderança petebista na cidade de São João da Boa Vista, São Paulo - Nicolau, Maria (2013)
The present research analyses the emerging leadership in the municipal district of São João da Boa Vista (SP) allied to Brazilian Labor Party (PTB) during the years of 1950. This person leader is called Miguel Jorge Nicolau descendent from an Arabic-Lebanese immigrant family and belonging to the rural quotidian of this town. He initiated his trajectory through the quotidian of the factory FIATECE, whose workers were especially women in their majority. Despite of the Arabic-Lebanese community other than seen as a group who had with them a certain restriction common to those typical inhabitants, and also for the unusual particularities from his private life, those which were very unconventional, though all this, Miguel Jorge Nicolau became a public man. He was elected for the city hall as a mayor and became later a regional representative in the Legislative House as a deputy for the PTB. Since then, he was seen with distrust by the political police, as a dangerous communist infiltrated in PTB or as a risk to the national security, and, based on these information, the agents of the dictatorship, in 1964, he had his political rights annulled. The documentation used for this research has the amount of interviews, newspaper articles, Annals from the Legislative House. We shall give attention to the last two sources as the outstanding discourses and speeches in the Chamber of Deputies